The impact of cloud technology on innovation capacity in banking - Sousa, Ricardo Coelho de (2022)
Cloud leveled competition and invited new entrants to capture a portion of the banking industry profits. To optimise resource allocation for the development of information technology (IT) organisations’ delivery capabilities, this study examines the impact of cloud flexibility on IT personnel capabilities and innovation. The study was conducted through an online survey of 167 IT practitioners in the IT organisations of banking and financial service firms collected between 31 July 2021 and 3 September 2021. The results revealed that cloud infrastructure flexibility has a strong positive effect on the capabilities of IT personnel. Furthermore, cloud infrastructure flexibility has a positive effect on IT organisations’ innovation capacity. Moreover, cloud infrastructure flexibility, although positively correlated with innovation capacity at the 95% significance level, does not have a statistically significant effect on innovation capacity (p-value: 0.285) and IT personnel capabilities have a medium effect (f2 : 0.252) on innovation capacity. Lastly, the indirect effect of cloud infrastructure flexibility on innovation capacity is significant. Overall, while innovation capacity is one important component of bank’s future superior performance and flexible cloud infrastructure is a key enabler of it, capabilities of IT personnel are crucial for banking innovation.